PENGARUH UPAYA –UPAYA PEMASARAN TERHADAP MINAT KONSUMEN Kasus Evaluasi Penjualan Produk Jasa Ekspedisi CV. Riau Anugrah Family Pekanbaru - Monika Safriani; Suryalena " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research was conducted in the CV . Grace Family Riau Pekanbaru . The setting ofthe problem is how to influence efforts - marketing efforts on consumer interest . The purpose ofthis study was to determine the effect of efforts - marketing efforts on consumer interest in CV .Grace Family Riau Pekanbaru.The author uses descriptive quantitative analysis method and some theories aboutPemasarn and Interests . Indicators used in the independent variables are product, price ,promotion , and place and the dependent variable is the interest . Collecting data usingquestionnaires , interviews and observations . The sample used is the census . Source of dataused is primary data or data obtained directly from the questionnaires and interviews . Secondarydata is data obtained from company documents CV .Grace Family Riau Pekanbaru . the results of this study indicate that there is significantbetween marketing variables on consumer interest . And the existence of a fairly strongrelationship between the variables and positive marketing of the consumer interest .Keywords : Marketing , interest , services